Analisis Deep Ecology Arne Naess terhadap Krisis Iklim dalam Buku Bumi yang Tak Dapat di Huni - Wilda Nur Rosyidah; Elma Desi Murohishoh; Siti Anisatul Mardhiah; Tri Utami Oktaviani (Pusat Riset dan Inovasi Nasional, 2025)
The climate crisis is no longer just a concern for environmental activists, but has evolved into a strategic threat affecting global stability. The climate crisis is now worsening into a serious threat to the sustainability of human life and the existing ecosystems on Earth. In his book,